Озерные страсти: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2021)
Экземпляры: (20210714) / Инвентарный номер: 41683 / Цена: 411.62 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6